If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + -3 = 13 + -9 Reorder the terms: -3 + 18x = 13 + -9 Combine like terms: 13 + -9 = 4 -3 + 18x = 4 Solving -3 + 18x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 18x = 4 + 3 Combine like terms: -3 + 3 = 0 0 + 18x = 4 + 3 18x = 4 + 3 Combine like terms: 4 + 3 = 7 18x = 7 Divide each side by '18'. x = 0.3888888889 Simplifying x = 0.3888888889
| 43r+50=60r | | -54-9x=36-12x | | X+235.12=310.21 | | x^2+7x+22=10 | | 1x-35=30 | | 8(10w+5)= | | -104-10x=50+x | | 10+5y=3y-9+2y | | -98-11x=175+10x | | 3g+21=6 | | 2x+8-6x=2x+44 | | -6*-6+5*-6-4= | | xsquared+2x-8=0 | | 8x-209=57-6x | | -12+6g=24 | | .2[10-5(x-2)]=.1(x+1) | | -3x-71=-10x+34 | | 6h-2(h+6)=10h | | 3x-4=2x+15 | | -9=x-4-6 | | 4(x+2)+x+1=2x-3+(3x+4) | | F+523.89=812.57 | | 3k+4k=-14 | | 9=3/5 | | -8-37=x | | -32+11x=73+4x | | 4x+205=14x-5 | | 3x+2(x+4)=-23 | | xsquared-14x+14=4-8x | | 2t+4t-2=26 | | 24x^2=18x | | x-1=-(1+x) |